Nigerian English - Jowitt, David (Dialects of English [DOE] ;, 2018)
Although the past few decades have witnessed growing interest in varieties of English around the world, no study of the Nigerian variety intended for the international market has yet been published.Making use of well-known paradigms, the book will relate Nigerian English, as a 'Second Language' variety, to other World Englishes. Its chief overall concern, however, is to provide a detailed descriptive account of the variety, seeking to show what is distinctive about it and also, in this perspective, distinguishing between more educated and less educated usage. After giving a sociolinguistic profile of Nigeria, where English today enjoys a more prominent role than ever before, it will examine in turn the phonology, morpho-syntax, and lexico-semantics of Nigerian English, with samples of written texts from the eighteenth century to the present. It will also give a comprehensive summary of academic research carried out in the field over the past fifty years.In this way the book will provide an introduction to the subject for the benefit of scholars and students in universities in many countries, and will serve as a useful companion to other books in De Gruyter Mouton's Dialects of English series.